2005
DOI: 10.1002/bdra.20105
|View full text |Cite
|
Sign up to set email alerts
|

Maternal folate deficiency results in selective upregulation of folate receptors and heterogeneous nuclear ribonucleoprotein-E1 associated with multiple subtle aberrations in fetal tissues

Abstract: Maternal folate deficiency results in selective upregulation of FR and hnRNP-E1 associated with multiple aberrations in fetal tissues that include increased cell loss, architectural anomalies, and premature differentiation. The potential significance of these findings to explain the wide spectrum of folate-responsive birth defects in humans is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 56 publications
5
60
0
Order By: Relevance
“…S3, E and H) to measure keratin 10 and filaggrin. Although there were subtle architectural abnormalities arising from disordered proliferation in the basal layers of HPV16-low folate-organotypic rafts when compared with HPV16-high folate-organotypic rafts, this was comparable with that seen in folate-deficient murine fetal epithelial tissues (23), where differentiation of keratinocytes in the skin was also retained.…”
Section: ((Hpv16)bc-1-ep/sl-hf) or Low Folate Medium ((Hpv16)bc-1-ep/supporting
confidence: 53%
“…S3, E and H) to measure keratin 10 and filaggrin. Although there were subtle architectural abnormalities arising from disordered proliferation in the basal layers of HPV16-low folate-organotypic rafts when compared with HPV16-high folate-organotypic rafts, this was comparable with that seen in folate-deficient murine fetal epithelial tissues (23), where differentiation of keratinocytes in the skin was also retained.…”
Section: ((Hpv16)bc-1-ep/sl-hf) or Low Folate Medium ((Hpv16)bc-1-ep/supporting
confidence: 53%
“…The apparent rebound effect of the Folr1 expression that occurred between 48 and 96 hr subsequent its initial knockdown is consistent with the magnitude of Folr1 up-regulation that can occur within 8 hr of the onset of a folate deficiency in several cell lines or in kidney cells (Hsueh and Dolnick, 1993;Said et al, 2000;Zhu et al, 2001;Sadasivan et al, 2002;Antony et al, 2004). Additionally, the expression of the folate receptor can be induced during folate insufficiency in some tissues where it is not normally expressed (Xiao et al, 2005). The increases in expression of this gene are thought to be due to both an increase in transcription rate and an increase in its RNA stability (Sadasivan, et al, 2002).…”
Section: Discussionsupporting
confidence: 57%
“…Fig. 7C documented a dose-dependent formation of RNAprotein complexes following the interaction of purified recombinant GST-hnRNP-E1 with either the 27-base TH mRNA ciselement or the 19-base NF-M mRNA cis-element in the presence of physiologically relevant concentrations of L-homocysteine found in murine dietary folate deficiency (52). Although the folate-replete murine fetal adrenal medulla (Fig.…”
Section: Promiscuity Of the Mrna-binding Site In Homocysteinylated Hnmentioning
confidence: 86%
“…Two independent laboratories have recently shown that hnRNP-E1/ PCBP1/␣CP1 can bind to cis-elements in the 3Ј-untranslated region of tyrosine hydroxylase (TH) mRNA (51) and the neuronal intermediate neurofilament-middle molecular mass (neurofilament-M, NF-M) mRNA (31) to induce a posttranscriptional up-regulation of these proteins; of significance, these investigators, as most others, employed artificial thiols (such as ␤-mercaptoethanol and/or DTT) to trigger these RNA-protein interactions. Accordingly, we determined if similar interactions could be triggered using physiologically relevant concentrations of L-homocysteine found in murine folate deficiency (52) and whether the functional consequences of RNA-protein interactions were detected by altered protein expression in the organs of gestation day 17 murine fetuses whose mothers had experienced gestational folate deficiency, having been fed a 400-nmol folate/kg diet for 2 months prior to and during pregnancy, when compared with control fetuses whose mothers were consistently fed a folate-replete diet composed of 1200 nmol folate/kg throughout. Fig.…”
Section: Promiscuity Of the Mrna-binding Site In Homocysteinylated Hnmentioning
confidence: 99%